Clinical Characteristics and Management of Functional Pancreatic Neuroendocrine Neoplasms: A Single Institution 20-Year Experience with 286 Patients - Yuqing Qu; Haoming Li; Xianling Wang; Yulong Chen; Qinghua Guo; Yu Pei; Jin Du; Jingtao Dou; Jianming Ba; Zhaohui Lv; Yiming Mu (International Journal of Endocrinology)
Background. Functional pancreatic neuroendocrine neoplasms (PanNENs) are very rare disorders but have complex spectrum, including insulinoma, gastrinoma, glucagonoma, somatostatinoma, and VIPoma. Patients with PanNENs usually present with characteristic symptoms caused by corresponding hormone hypersecretion. It has always been challenging in dealing with such rare but complicated disorders. In this report, we analyzed the clinical characteristics of functional PanNENs in a large cohort of Chinese patients and summarized our clinical experience in diagnosis and treatment. Methods. The retrospective analysis was performed in patients with a definite diagnosis of functional PanNENs hospitalized in Chinese PLA General Hospital between 2000 and 2020. The clinical characteristics, surgical information, and pathological findings were extracted from their medical records and were analyzed. Results. Totally, 286 patients (gender: male 103 and female 183; age: 45.55 ± 15.23 years old) were diagnosed with definite functional PanNENs. The most frequent functional PanNENs were insulinoma (266/286) followed by glucagonoma (10/286), somatostatinoma (3/286), adrenocorticotropic hormone- (ACTH-) producing tumor (3/286), gastrinoma (2/286), and VIPoma (2/286). Nine patients were diagnosed with multiple endocrine neoplasia type 1 (MEN1) in which all the associated functional PanNENs were insulinomas. The duration from symptoms’ onset to confirmed diagnosis was 3.67 ± 4.28 years. Two hundred and eighty patients with tumor localized in pancreatic or with limited metastasis underwent surgery. The symptoms associated with hormonal oversecretion were improved significantly after surgery. Five patients with unresectable metastases or tumor recurrence after surgery were administrated with systemic chemotherapy or other targeted therapies. With these various therapies, the symptoms were also partially relieved. According to findings in pathological and immunochemical examination, all the functional PanNENs were categorized into NEN-G1 (41.95%), NEN-G2 (54.90%), NEN-G3 (3.15%), and NEC-G3 (0%). Conclusion. Patients with suspected functional PanNENs should have a systematic endocrine examination at diagnosis. Multidisciplinary collaborations are essential for precise diagnosis and tumor localization. A successful surgery or other targeted therapies can improve the prognosis of patients with such rare but complex disorders.